APPLICATION OF COOPERATIVE LEARNING MODEL TYPE THE POWER OF TWO TO IMPROVE STUDENT LEARNING SOCIAL STUDIES - Nurbaini Nurbaini (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This study was initiated by the low learning outcomes of social studies students at SDN 002 Muara Lembu. The purpose of this research is to improve students' social studies learning outcomes by applying the power of two cooperative learning model. This research was conducted at SDN 002 Muara Lembu. When the research was conducted in the even semester of the 2018/2019 school year. The subjects of this study were students of class IV.B SDN 002 Muara Lembu with a total of 22 students consisting of 13 male students and 9 female students. This type of research is a classroom action research study consisting of two cycles, each cycle consisting of planning, implementation, observation and reflection. The results of research conducted to prove that, student learning outcomes have increased, from an average base score of 62.7 increased to 73.2 in Cycle I and increased again in cycle II to 87.3. Overall, there was an increase from the baseline score to End of Cycle II at 35.1%. From these results, it can be concluded that by applying the power of two types of cooperative learning model can improve the social learning outcomes of students in grade IV.B SDN 002 Muara Lembu.